1996
DOI: 10.1254/jjp.70.235
|View full text |Cite
|
Sign up to set email alerts
|

Restricted Propagation of Cytoplasmic Ca2+ Oscillation into the Nucleus in Guinea Pig Cardiac Myocytes as Revealed by Rapid Scanning Confocal Microscopy and Indo-1

Abstract: ABSTRACT-Two-dimensional images of cytoplasmic and nuclear free Ca2+ movements in cardiac myo cytes were obtained at 67-msec intervals using a Ca2+-sensitive fluorescence probe, indo-1, and a rapid scanning confocal laser microscope, Nikon RCM8000. Isolated guinea pig ventricular cells were loaded with indo-1 and stimulated at 0.5 Hz through patch pipettes. On stimulation, nuclear Ca2+ concentration ([Ca2+]) was observed to rise and fall following cytoplasmic [Ca2+] with an obvious delay. Application of isopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…This difference could be explained by localization of acetoxymethyl derivatives of fluoroprobes to cytoplasmic organella such as the mitochondria and SR. 13) Our results that fluorescence in the cytoplasm and nucleus were quenched by Mn 2ϩ to a simillar extent may suggest that Mn 2ϩ enters some of these organella. Rapid cooling contracture was considered to be a kind of relaxation between different steady-state levels of SR Ca 2ϩ uptake, 14) and Mn 2ϩ was reported to inhibit myocardial ATP-dependent Ca 2ϩ transport.…”
Section: Discussionmentioning
confidence: 64%
“…This difference could be explained by localization of acetoxymethyl derivatives of fluoroprobes to cytoplasmic organella such as the mitochondria and SR. 13) Our results that fluorescence in the cytoplasm and nucleus were quenched by Mn 2ϩ to a simillar extent may suggest that Mn 2ϩ enters some of these organella. Rapid cooling contracture was considered to be a kind of relaxation between different steady-state levels of SR Ca 2ϩ uptake, 14) and Mn 2ϩ was reported to inhibit myocardial ATP-dependent Ca 2ϩ transport.…”
Section: Discussionmentioning
confidence: 64%
“…The increases in cytosolic Ca 2ϩ were initially thought to be transmitted passively to the nucleus via Ca 2ϩ diffusion through nuclear pore complexes (31)(32)(33). More recent studies showed that cardiomyocytes contain a separate membrane source around and within the nucleus that is sensitive to IP 3 (2, 14, 22, 24, 25, 29).…”
Section: Discussionmentioning
confidence: 99%
“…The spatial nonuniformity lasts only for about 4 ms, and at about 10 ms after stimulation, the Ca 2+ concentration is elevated throughout the cytoplasm. Nuclear Ca 2+ was observed to rise and fall following cytoplasmic Ca 2+ with a delay, which could be best explained by the nuclear envelope acting as a diffusion barrier (4). Comparison of transmission image of striations with line scanned Ca 2+ images revealed that points where the rise in Ca 2+ was fast coincided to the center of the I-band (Z-line), and the points where the rise in Ca 2+ was slow coincided to the center of the I-band (A-line).…”
Section: Excitation-contraction (E-c) Coupling In Ventricular Myocytesmentioning
confidence: 98%